Approaches for the leveraging small and medium enterprises to improve nutrition: A net-map assessment of actors and activities in Ghana - Food and Agricultural Organization of the United Nations; International Food Policy Research Institute; Aberman, Noora-Lisa (Food and Agricultural Organization of the United Nations, 2021)
This report presents the outcomes of a workshop organized by IFPRI and FAO in Ghana; it represents the result of a wider process of analysis and interventions aiming to leverage the role of small and medium-sized enterprises to improve nutrition in Ghana. The information provided may prove useful for researchers, practitioners, international organizations and policy-makers in planning interventions, designing policies or analyzing contexts other than Ghana.